Analysis of Human Brain Structure Reveals that the Brain “Types” Typical of Males Are Also Typical of Females, and Vice Versa - Joel, Daphna; Persico, Ariel; Salhov, Moshe; Berman, Zohar; Oligschläger, Sabine; Meilijson, Isaac; Averbuch, Amir (Frontiers in Human Neuroscience, 2018)
Findings of average differences between females and males in the structure of specific brain regions are often interpreted as indicating that the typical male brain is different from the typical female brain. An alternative interpretation is that the brain types typical of females are also typical of males, and sex differences exist only in the frequency of rare brain types. Here we contrasted the two hypotheses by analyzing the structure of 2176 human brains using three analytical approaches. An anomaly detection analysis showed that brains from females are almost as likely to be classified as ‘normal male brains’, as brains from males are, and vice versa. Unsupervised clustering algorithms revealed that common brain ‘types’ are similarly common in females and in males and that a male and a female are almost as likely to have the same brain ‘type’ as two females or two males are. Large sex differences were found only in the frequency of some rare brain ‘types’. Last, supervised clustering algorithms revealed that the brain ‘type(s)’ typical of one sex category in one sample could be typical of the other sex category in another sample. The present findings demonstrate that even when similarity and difference are defined mathematically, ignoring biological or functional relevance, sex category (i.e., whether one is female or male), is not a major predictor of the variability of human brain structure. Rather, the brain types typical of females are also typical of males, and vice versa, and large sex differences are found only in the prevalence of some rare brain types. We discuss the implications of these findings to studies of the structure and function of the human brain.